Ultrasound feature variants of the adductor longus tendon in asymptomatic sportive subjects: Management implications - Dallaudiere, Benjamin; Sylvain, Bise; Poussange, Nicolas; Reboul, Gilles; Silvestre, Alain; Meyer, Philippe; Hocquelet, Arnaud; Pesquer, Lionel (European journal of radiology, 2021)
The potential contribution of ultrasound (US) to diagnose adductor longus (AL) tendinopathy in athletic pubalgia requires clarification. We investigate US findings from AL tendons of asymptomatic participants to identify the range and prevalence of common US features not associated with groin pain. We consecutively enrolled 45 volunteers physically active participants with no history of groin pain. US features of bilateral AL tendons were investigated and recorded by two experienced musculoskeletal radiologists (MSKR) in accordance with a defined ultrasound protocol. Two other MSKRs retrospectively and independently analyzed all US images. Ninety AL tendons from 45 participants (4/45 women) were imaged (average age: 35 years ±14.6; dominant side: 37/45 (82.2%) right, 8/45 (17.8%) left). Abnormalities on US were found in all 45 (100%) AL tendons, including: abnormal echogenicity (98.9%/100% respectively according to reader), loss of fibrillar structure (92.2%/97.8%), irregularities of the superficial paratendon (23.3%/30%), calcifications (22.2%/25.5%), and cortical erosion (52%/55.5%), with excellent inter-observer assessment. No AL tears or hyperemia at color Doppler were detectable. AL tendon abnormalities were identified via US in 100% of our asymptomatic athletes. The significance of these US findings should be interpreted cautiously with respect to clinical presentation. On the other hand, there is a need for supplemental investigation into the clinical relevance of US AL tendon tears not present in the present asymptomatic athlete population.